Avaliação da metodologia de classificação SARA de óleos brutos e estudo da redução de escala - Silva, Schnaider Shayane Vieira da (2016)
Petroleum or crude oil is a complex mixture formed by aliphatic, aromatic and naphthenic hydrocarbon, and other compounds containing sulfur, oxygen, nitrogen, and organometallic constituent complexed with nickel and vanadium. To crude oil characterization the separation by classes SARA (saturated, aromatics, resins and asphaltenes) is one of the most applied method. This method presents certain disadvantages such as excessive expense of solvents, adsorvents and lenghty analysis time. In this context, this study aims to evaluate the SARA fractionation efficiency by the conventional method and by reducing scale. In this study, it was used 7 different samples of crude oil from Carmópolis field from the Mercês and Jericó stations, provided by advanced recovery process with steam injection. The miniaturization of the SARA method has shown promise in relation to the conventional technique, meeting the criteria of the methodology and presenting recovery between 87-98%. Analysis by GC/MS contributed to confirm the efficiency of the separation of fractions by the macro and micro column through selective ion monitoring (m/z 142, 156 and 170). The relative areas for both the GC-FID and by GC-MS chromatograms showed to the fractions of macro and micro column that the fraction of saturated compounds compared with Malteno showed similar relative profiles and areas, demonstrating that the gas chromatographic system is inappropriate to the analysis of aromatic and resin fraction. However, the aromatic (15-19%) and resin fraction (14-16%), when analyzed separately, showed no relative areas equivalent to the isolated gravimetric percentage, confirming the discrimination of the chromatographic system to more polar fractions of oils.